Cryptococcal meningitis is a cause for cross‐reactivity in cerebrospinal fluid assays for anti‐Histoplasma, anti‐Coccidioides and anti‐Blastomyces antibodies. Issue 3 (1st January 2019) - Bahr, Nathan C.; Panackal, Anil A.; Durkin, Michelle M.; Smedema, Melinda L.; Keown, Wesley; Davis, Thomas E.; Raymond‐Guillen, Luke; Park, Yoon‐Dong; Marr, Kieren A.; Fries, Bettina C.; Williamson, Peter R.; Boulware, David R.; et al.
Summary: Background/Objectives: Antibody detection is commonly used for diagnosis of histoplasmosis, and cross‐reactions have been recognised due to endemic mycoses but not cryptococcosis. We observed cross‐reactions in an anti‐ Histoplasma antibody enzyme immunoassay (EIA) in the cerebrospinal fluid (CSF) from a patient with cryptococcal meningitis and sought to assess the risk of cross‐reactive anti‐ Histoplasma antibodies in persons with cryptococcal meningitis. Methods: An anti‐cryptococcal antibody EIA was developed to measure CSF antibody response in HIV‐infected subjects from Kampala, Uganda and previously healthy, HIV‐negative subjects at the National Institutes of Health (NIH) with cryptococcal meningitis. Specimens were tested for cross‐reactivity in assays for IgG anti‐ Histoplasma, anti‐ Blastomyces and anti‐ Coccidioides antibodies. Results: Among 61 subjects with cryptococcal meningitis (44 Kampala cohort, 17 NIH cohort), elevated CSF anti‐cryptococcal antibody levels existed in 38% (23/61). Of the 23 CSF specimens containing elevated anti‐cryptococcal antibodies, falsely positive results were detected in antibody EIAs for histoplasmosis (8/23, 35%), coccidioidomycosis (6/23, 26%) and blastomycosis (1/23, 4%). Overall, 2% (2/81) of control CSF specimens had elevated anti‐cryptococcal antibody detected, both from Indiana. Conclusions: Cryptococcal meningitis may cause false‐positive results in the CSF for antibodies against Histoplasma, Blastomyces and Coccidioides . Fungal antigen testing should be performed to aid in differentiating true‐ and false‐positive antibody results in the CSF.